Activated Carbon from Waste Coffee Grounds for Effective Methylene Blue Removal in Textile Wastewater Treatment - Ilmawati, Wa Ode Sitti; Nurmayasari, Nurmayasari; Purnawati, Diki; Sholihun, Sholihun; Nugraheni, Ari Dwi (Trends in Sciences, 2025)
Utilizing waste coffee grounds (WCGs) to produce activated carbon (WCGs-AC) supports sustainable waste management by converting organic waste into value-added materials. This study investigates the optimization of the production process, physicochemical properties, and adsorption performance of activated carbon derived from WCGs. This study pretreated WCGs using hexane and hot water washing methods, followed by carbonization under oxygen-limited conditions. The resulting WCGs-AC exhibited grain sizes ranging from 1.34 to 1,376.00 nm, high specific surface areas (1,304 - 3,405 m²/g), pore volumes of 1.262 - 4.079 cm³/g, and average pore radii between 1.936 and 2.397 nm. Functional groups such as amine (N–H), hydroxyl (–OH), and C–O were identified on the WCGs-AC surface. All WCGs-AC samples achieved 100% Methylene Blue (MB) removal, with similar adsorption capacities ranging from 10.20 ± 0.00 to 10.74 ± 0.02 mg/g. The highest-performing adsorbent was obtained using the hot water washing method and carbonization at 550 °C (WZ550), which exhibited an effectively infinite adsorption rate and sustained 100% removal efficiency over 6 reuse cycles. Various kinetic models, including pseudo-1st-order (PFO), pseudo-2nd-order (PSO), Elovich, and Weber-Morris, were applied to describe the adsorption behavior. These findings demonstrate that low-cost and efficient adsorbents can be derived from coffee waste, offering promising potential for dye removal in textile wastewater treatment. HIGHLIGHTS WCGs are extracted by the hot water and hexane washing method, then carbonized without a gas flow. The activated carbon showed large surface areas, 1,300 - 3,400 m²/g The WZ550 demonstrated sustained 100% removal efficiency across 6 reuse cycles Adsorption kinetics fixed to the PSO model with R2 = 1 GRAPHICAL ABSTRACT